Conspiracy - Gillot, Nick; Mandel, Loring; Pierson, Frank (HBO Home Video; distributed in the Philippines by Warner Home Video (Philippines), 2004)
On January 20, 1942, 15 German officials attended a conference at Wannsee - on the outskirts of Berlin. The meeting comprised of mid-ranking SS commanders and a variety of government ministers. The meeting was organized by SS Major Adolf Eichmann under the direction of Chief of Security Reinhard Heydrich. It was a polite conference, but under this thin veneer of manners lay an evil intent. By the end of the meeting, the fate of six million lives would be decided and the shape of the world would be altered forever.